A Novel Banana Mutant “RF 1” (Musa spp. ABB, Pisang Awak Subgroup) for Improved Agronomic Traits and Enhanced Cold Tolerance and Disease Resistance - Wang, Xiaoyi; Wang, Anbang; Li, Yujia; Xu, Yi; Wei, Qing; Wang, Jiashui; Lin, Fei; Gong, Deyong; Liu, Fei; Wang, Yanting; Peng, Liangcai; Li, Jingyang (Frontiers in Plant Science, 2021)
Banana is a major fruit crop grown in tropical and subtropical regions worldwide. Among cultivars, ‘FenJiao’ (Musa Spp. ABB, Pisang Awak subgroup) is a popular variety of banana, due to its better sugar-acid blend and relatively small fruit shape. However, because the traditional FenJiao variety grows relatively high in height, it is vulnerable to lodging and unsuitable for harvesting. In this study, we sought desirable banana mutants by carrying out ethyl methanesulfonate (EMS) mutagenesis with the FenJiao cultivar. After the FenJiao shoot tips had been treated with 0.8% (v/v) EMS for 4h, we obtained a stably inherited mutant, here called ‘ReFen 1’ (RF1), and also observed a semi-dwarfing phenotype. Compared with the wild type (FJ), this RF1 mutant featured consistently improved agronomic traits during 5-year field experiments conducted in three distinct locations in China. Notably, the RF1 plants showed significantly enhanced cold tolerance and Sigatoka disease resistance, mainly due to a substantially increased soluble sugars’ content and greater starch accumulation along with reduced cellulose deposition. Therefore, this study not only demonstrates how a powerful genetic stategy can be used in fruit crop breeding, but also provides insight into the identification of novel genes for agronomic trait improvement in banana and beyond.